(untitled) (Research, Society and Development, 2020)
The main purpose of this work is to study the heat transfer in an elliptical cylindrical reactor with a bed filled with particles. A heterogeneous mathematical model (two-phase model) was developed, applied to the solid and fluid phases separately. To solve the partial differential equations, the finite volume method, the fully implicit formulation, and the WUDS scheme for convective and diffusive terms were used. Results of temperature distribution in the fluid and solid phases, along the reactor, for particles with prolate spheroidal and spherical shape are presented and analyzed. It was found that the shape of the particle that fills the porous bed slightly affects the temperature distribution inside the reactor and that the dimensionless temperature of the fluid phase is slightly lower than that of the solid phase.